A Comparative Clinical Study to Evaluate the Efficacy of Dhatri Lauha and Murvadi Yoga in the Management of Pandu Roga w.s.r to Iron Deficiency Anemia (AYUSHDHARA, 2025)
Pandu is Varnopalakshita vyadhi. Vata and Kapha with Pitta as the predominant one aggravate in the Dhatus, as a result Dhatus become weak and heavy. By the vitiation of Doshas and Dhatus leads to the reduction in the properties of Ojas and leading to the symptoms like loss of complexion, strength etc leading to Pandu roga. Pandu roga is characterised by pale colour, depletion of blood and fat, weakness, weakened sense organs etc which can be correlated to Iron deficiency anemia. Iron deficiency anemia is the most common type of anemia worldwide. This occurs when iron or physiological requirements exceed absorption. This is the commonest nutritional deficiency and a major health problem globally. More than half of patients with anaemia are assumed to have iron deficiency. Between 30% and 70% population in the developing world is iron deficient. Ayurveda has a good approach in treating the Pandu roga. Acharyas have mentioned both Shodhana and Shamana line of treatment for Pandu roga. Hence the present study intends to clinical evaluation of the therapeutic effect of the formulation in patients of Pandu roga.